The effect of problem -based learning in secondary schools - MEKHALDI, MOHAMMED (My University, 2019)
The present dissertation attempts to investigate the role of problem-based learning approach (PBL) in motivating learners and increasing educational level. It is hypothesized in this work that the PBL approach can help teachers and learners to work in collaborative atmosphere and get many benefits from its implementation in classroom practice. The main objective is to highlight the significance of PBL approach implementation to increase learners’ motivation unlike deductive traditional methods. In this case, teachers are encouraged to adopt this technique whenever needed. Two questionnaires were administered to the three secondary schools in Relizane-S’hihMhamed of Ramka,Omar Ibn Elkhatab and Elmanar secondary school in Ammi Moussa-We intend to explore learners’ and teachers’ attitudes towards PBL. The results showed that most teachers do believe that PBL approach generally has a great impact on the learning process. Hence, it increases their motivation to learn and to become more active. In addition, the results demonstrated that (PBL) has enormous positive effects on schools that use it on a regular basis regardless of the obstacles that they may face like overcrowded classes.
Case Study of Secondary Schools in Relizane
Keywords: PBL problem-based learning; FL foreign languages; TM traditional methods; CM classroom management; LM learning methods